(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This study systematically reviews and bibliometrically maps the scholarly literature on eco-efficiency mechanisms associated with green technology adoption in the textile industry, identifying institutional barriers, theoretical frameworks, and conceptual solutions underpinning the sector’s green transformation. A systematic literature review (SLR) following PRISMA 2020 guidelines was conducted. Scopus and Web of Science databases were searched using targeted keyword combinations. From an initial pool of 701 records, 127 articles published between 2000 and 2024 were selected after rigorous screening. Bibliometric analysis including co-citation mapping, keyword co-occurrence, and thematic clustering was performed using VOSviewer. Thematic content analysis followed the Braun and Clarke (2006) framework.